232 − 172 = 529 − 289 = 240
232 − 172 = (23 + 17)(23 − 17) = (40)(6) = 240
232 − 172 = (23 − 17)2 = (6)2 = 36
Answer:
Your answer is 23^2 − 17^2 = (23 + 17)(23 − 17) = (40)(6) = 240, or C on your answer sheet.
Step-by-step explanation:
Lets begin!
So when a binomial is composed of two perfect squares separated by a subtraction symbol, a certain method called the difference of perfect squares can be used. The difference of perfect squares method can be done by multiplying the sum and difference of the two square roots.
So, to solve:
23^2 - 17^2 = (23 + 17)(23-17) = (40)(6) = 240
Thus being your answer.
Always here to help a Brainly citizen! (✪㉨✪) Sincerely, Kelsey from Brainly
~ #LearnWithBrainly ~
6x - 15 = -3y
2) 6y + 2x = 8
12y + 4x = 4
The correct classification of the given equations is as follows:
This refers to the system of equations where an equation has infinite solutions and has more than one form on a given line.
With this in mind, we can see that when we are given a system of equations such as
5 - y = 2x
6x - 15 = -3y, then we know that this is a dependent equation because of the infinite solutions on the two equations.
Read more about dependent equations here:
brainly.com/question/10417850
A 30 20
B 52 48
What conclusion can be drawn about the number of trials and the probability of the coin landing on heads or tails?
Answer:
2/7
Step-by-step explanation:
7 days in a week
Out of which, 2 are weekend
P(weekend) = 2/7